Closed Bipolar Electrochemistry for the Detection of Human Immunodeficiency Virus Short Oligonucleotide. (20th December 2016) - Poorghasem, Roghayeh; Saberi, Reyhaneh Sadat; Shayan, Mohsen; Mehrgardi, Masoud A.; Kiani, Abolfazl
Abstract: Although a monumental progress has been made in case of Human Immunodeficiency Virus researches, there are still more than 34 million people living with this viral disease. Therefore, the development of a fast and cost-effective protocol that can sensitively and selectively detect HIV gene sequence is essential. In the present study, a protocol for the molecular detection of HIV genome taking advantage of closed bipolar electrochemistry integrated with electrogenerated chemiluminescence detection is described. In this case, a closed split bipolar electrochemical cell is applied to detect the short specific oligonucleotide target of HIV1. Anthraquinone disulfonic acid, as a negative electroactive reporter, intercalates with hybridized double-strand DNA on the sensing site. By reduction of redox reporter (AQDS) on the cathodic pole, luminol is oxidized on the anodic pole and subsequent oxidized diazo product generates light that is followed using a photomultiplier tube. The experimental condition is optimized to obtain the highest sensitivity. The results demonstrate the high sensitivity and selectivity of this fast and economical method toward Human Immunodeficiency Virus genome detection in the range of 0.1 to 300 nM with the detection limit of 30 pM (S/N = 3).